Studies on The illuminated chronicle - Bak, János M.; Bak, János M.; Veszprémy, László; Veszprémy, László (Central European medieval texts, 2018)
Cover; Title page; Copyright page; Contents; Abbreviations; List of Illustrations; Preface; Orsolya Karsay: The Codex of the Illuminated Chronicle; János M. Bak and Ryszard Grzesik: The Text of the ""Chronicle of the deeds of the Hungarians; Ernő Marosi: The Illuminations of the Illuminated Chronicle; György Rácz: The Heraldry of Angevin-age Hungary and its Reflections in the Illuminated Chronicle; Martyn Rady: Attila and the Hun Tradition in Hungarian Medieval Texts; Dániel Bagi: The Dynastic Conflicts of the Eleventh Century in the Illuminated Chronicle